2023
DOI: 10.3390/f14040668
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Trees with Different Growth Statuses to Pruning on a Pinus massoniana Lamb. Plantation

Abstract: Pruning is an important technique in culturing good knot-free timber. However, to make more accurate pruning plans, it is necessary to consider the growing status of trees and set reasonable pruning intensities based on this. In a seven-year-old Pinus massoniana Lamb. plantation, we carried out pruning twice with a time interval of two years. The treatments included one unpruned treatment (CK) and five pruned treatments (from P1 to P5, representing the live branch height being kept at 68%, 55%, 60%, 55% and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The results of Ferrere et al (2015) in P. radiata plantations, with density equal to that of this study (around 1 100 plants•ha -1 ), reveal that reducing the plantation density to 50 % plus a 40 % pruning of the live crown results in a loss of productivity. On the other hand, it has been reported that trees with different growth capacity respond differently to pruning intensity; for example, in Pinus massoniana Lamb., and height respond better with light pruning in weak trees, while vigorous trees respond better with severe pruning (Zhao et al, 2023).…”
Section: Volume Increase (Mmentioning
confidence: 95%
See 1 more Smart Citation
“…The results of Ferrere et al (2015) in P. radiata plantations, with density equal to that of this study (around 1 100 plants•ha -1 ), reveal that reducing the plantation density to 50 % plus a 40 % pruning of the live crown results in a loss of productivity. On the other hand, it has been reported that trees with different growth capacity respond differently to pruning intensity; for example, in Pinus massoniana Lamb., and height respond better with light pruning in weak trees, while vigorous trees respond better with severe pruning (Zhao et al, 2023).…”
Section: Volume Increase (Mmentioning
confidence: 95%
“…Los resultados de Ferrere et al (2015) en plantaciones de P. radiata, con densidad igual a la de este estudio (alrededor de 1 100 plantas•ha -1 ), revelan que la reducción de la densidad de la plantación al 50 % más una poda del 40 % de la copa viva se traduce en una pérdida de la productividad. Por otro lado, se ha reportado que los árboles con capacidad diferente de crecimiento responden de manera distinta con respecto a la intensidad de poda; por ejemplo, en Pinus massoniana Lamb., el incremento y altura responden mejor con podas ligeras en árboles débiles, mientras que los árboles vigorosos responden mejor con podas severas (Zhao et al, 2023).…”
Section: Pruning Intensity and Its Effect On Epicormic Shoot Emissionunclassified